2016
DOI: 10.3389/fphys.2016.00162
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Brain's Macro- and Micro-Circulatory Blood Flow Responses to CO2 via Transfer Function Analysis

Abstract: Objectives: At present, there is no standard bedside method for assessing cerebral autoregulation (CA) with high temporal resolution. We combined the two methods most commonly used for this purpose, transcranial Doppler sonography (TCD, macro-circulation level), and near-infrared spectroscopy (NIRS, micro-circulation level), in an attempt to identify the most promising approach.Methods: In eight healthy subjects (5 women; mean age, 38 ± 10 years), CA disturbance was achieved by adding carbon dioxide (CO2) to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Contrary to other studies, 5 we found a significant agreement between microvascular and macrovascular phase difference estimates of cerebral autoregulation in the LF band, which is to the best of our knowledge a unique finding which has never been reported in the literature. Other studies that have directly compared microvascular with macrovascular estimates of DCA have reported correlations with MABP and NIRS variables only 11,40 and did not evaluate agreement (i.e. ICC analysis) but reported associations or correlations.…”
Section: Cerebral Autoregulation Estimates With Tt-bf/bv Correctionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to other studies, 5 we found a significant agreement between microvascular and macrovascular phase difference estimates of cerebral autoregulation in the LF band, which is to the best of our knowledge a unique finding which has never been reported in the literature. Other studies that have directly compared microvascular with macrovascular estimates of DCA have reported correlations with MABP and NIRS variables only 11,40 and did not evaluate agreement (i.e. ICC analysis) but reported associations or correlations.…”
Section: Cerebral Autoregulation Estimates With Tt-bf/bv Correctionmentioning
confidence: 99%
“…Discrepancies between both types of DCA estimates have been reported, 5 but direct comparisons between microvascular-and macrovascular-based DCA estimates with simultaneous measurements of all relevant variables have rarely been described. [9][10][11] If microvascular-and macrovascular-based estimates of DCA were similar, this would be of considerable practical importance, since the feasibility of non-invasive continuous autoregulation monitoring and guided therapy in clinical situations would certainly increase with easy to apply NIRS methodology. 12 An important difference between the microvascular and macrovascular measurements is that microvascular measurements are part of a serial system, while macrovascular measurements can be viewed as a parallel system; except for frequencies in the autoregulation range, oscillations in MABP and CBFV arrive at their measurements sites simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…The CVR decrease seems in agreement with current concepts of neurovasal interaction derived from functional magnetic resonance imaging and from near infrared studies (Huber et al 2017, Petridou et al 2017, Schmid et al 2017: with the beginning of the task a vasodilation occurs which leads to an increase in cerebral blood volume and an increase in the concentration of oxygenated blood which is considered to represent an increase in CBF. When such a vasodilation is induced by CO 2 , in dCA the vasodilatory response consists usually of a phase decrease while gain remains not significantly changed (Müller et al 2016, Panerai et al 1999, Zhang et al 1998). Thus, the phase decrease findings in our population could be the result of vasodilation.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral autoregulation has been found to be damaged in several conditions including head injury, 12 ischemic stroke, 5 and subarachnoid hemorrhage. 23 , 24 This vicious cycle imposes fluctuations in perfusion pressure in the brain and is associated with worse prognosis.…”
Section: Discussionmentioning
confidence: 99%